Evolutionary analysis of SARS-CoV-2 spike protein for its different clades - Pereson Moschen, Matias Javier (2021)
The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the main target for antiviral and vaccine development. Despite its relevance, e information is scarse about its evolutionary traces. The aim of this study was to investigate the diversification patterns of the spike for each clade of SARS-CoV-2 through different approaches. Two thousand and one hundred sequences representing the seven clades of the SARS-CoV-2 were included. Patterns of genetic diversifications and nucleotide evolutionary rate were estimated for the spike genomic region. The haplotype networks showed a star shape, where multiple haplotypes with few nucleotide differences diverge from a common ancestor. Four hundred seventy-nine different haplotypes were defined in the seven analyzed clades. The main haplotype, named Hap-1, was the most frequent for clades G (54%), GH (54%), and GR (56%) and a different haplotype (named Hap-252) was the most important for clades L (63.3%), O (39.7%), S (51.7%), and V (70%). The evolutionary rate for the spike protein was estimated as 1.08 × 10−3 nucleotide substitutions/site/year. Moreover, the nucleotide evolutionary rate after nine months of the pandemic was similar for each clade. In conclusion, the present evolutionary analysis is relevant as the spike protein of SARS-CoV-2 is the target for most therapeutic candidates; besides, changes in this protein could have consequences on viral transmission, response to antivirals and efficacy of vaccines. Moreover, the evolutionary characterization of clades improves knowledge of SARS-CoV-2 and deserves to be assessed in more detail as re-infection by different phylogenetic clades has been reported.